PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA BANK NEGARA INDONESIA (BNI) CABANG PALANGKA RAYA - Mahrawati Mahrawati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Increasingly rapid competition leads to organizational awareness on importanceof having qualified, integrated and high committed human resources with ability tosupport organizational performance in general. Thus, it is necessary for organization tolook for any factors that can improve employee work motivation, one of which is byimprovement on employee work productivity.From the above description, the author tries to study the influences of extrinsicmotivation on the improvement on employee work productivity in Bank NegaraIndonesia (BNI) Branch of Palangka Raya. The research aims to find out description ofwork motivation influences on employee productivity. In this study, the method usedis descriptive method with survey method approach. Data collection techniques usedby the author are library research to obtain secondary data, and field research in orderto obtain primary data by interview technique.From results of this study, it indicates that the influences of motivation hassignificant influences on improving employee work productivity with the calculationresults of the analysis show that the determination value is 0.90, which means the levelof incentives on work motivation has 100% positive influences, which means thehypothesis can be accepted.